(untitled) (International Journal of Engineering and Computer Science, 2017)
In today’s world most of the communication is done electronic media. Data security plays vital role in such communication. Hence there is need to protect data from malicious attack. This can be achieved by cryptography. The earlier encryption algorithm was DES which has several loopholes such as small key size, sensible to brute force attack etc. These loopholes were overcome by AES algorithm. AES was announced by NIST (National institute of standard and technology) in November 2001. AES became the successor of DES algorithm because of its security, its ease of implementation, and low memory requirements. There are three different versions of AES. Each of them has block length 128 bits and key length is 128, 192 and 256 bits